Kajian Kitab Tafsir dalam Jaringan Pesantren di Jawa Barat - Rosihon Anwar; Dadang Darmawan; Cucu Setiawan (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2016)
Tafsir is one of the essences of Islamic orthodoxy and its authenticity is always guarded. Therefore, a drastic change is avoided in the studies of tafsir especially in pesantren, because pesantren is the institution that most persistent in guarding the Islamic orthodoxy in Indonesia. Not surprisingly, this research that was conducted in 2015 foundssimilarity to what has been reported by Berg in the nineteenth century and by Bruinessen and other researchers in the twentieth century. This article is the report of field research conducted at six pesantren in West Java namely: Pesantren al-Jawami Bandung, Pesantren al-Wafa Bandung, Pesantren al-Masthuriyah Sukabumi, Pesantren Darusalam Ciamis, Pesantren Cipasung Tasikmalaya and Pesantren Buntet Cirebon. This research focus on the study of tafsir books in these pesantren. This research concluded that changes do exist and occur in the study of tafsir in these pesantren, but extremely slow. The study of tafsir is still considered a second choice in pesantren compare to the study of fiqh and Arabic language. The most popular tafsir studied in these pesantren is Tafsir Jalalayn. There are also pesantren where other tafsir were studied like Tafsir al- Manar and Tafsir al-Maraghy, but very rare; that is in pesantren oriented to modernity. In addition, the traditional method of studying tafsir is still dominant in this pesantren, called bandongan where the Kyai (leader of pesantren) annotate the text word by word in front of the students (santri).